2007
DOI: 10.1063/1.2433707
|View full text |Cite
|
Sign up to set email alerts
|

Nickel silicide formation using multiple-pulsed laser annealing

Abstract: The effect of multiple-pulsed laser irradiation on Ni silicide formation in Ni(Ti)∕Si system was studied. A layered structure consisting of both crystalline NiSi2 and Ni-rich Ni–Si amorphous phases with a protective TiOx overlayer was formed after five-pulsed laser annealing at 0.4Jcm−2. Different solidification velocities caused by a variation in the atomic concentration across the melt have led to the formation of this layered structure. On the other hand, by increasing the number of laser pulses, a continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In the attempt to separate these effects, the authors had conducted pulsed laser SEE tests without biasing of the device and still observed laser induced damages at relatively similar laser energies. In the absence of electric field, several other research groups [12][13][14] had already demonstrated that pulsed laser was capable of inducing annealing effects on nickel silicide layers. However, these were demonstrated via pulsed laser of much shorter wavelengths (or higher photon energy) which were less than 355 nm and longer pulse duration (10 to 150 ns) than the pulsed laser utilized in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…In the attempt to separate these effects, the authors had conducted pulsed laser SEE tests without biasing of the device and still observed laser induced damages at relatively similar laser energies. In the absence of electric field, several other research groups [12][13][14] had already demonstrated that pulsed laser was capable of inducing annealing effects on nickel silicide layers. However, these were demonstrated via pulsed laser of much shorter wavelengths (or higher photon energy) which were less than 355 nm and longer pulse duration (10 to 150 ns) than the pulsed laser utilized in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid melting and resolidification process during PLA probably prevents redistribution of the atoms within the melt, hence resulting in a graded Ni-Si profile within the silicide. While Ni-rich silicide is formed at 300 mJ/cm 2 , transformation of Ni-rich silicide to low resistive NiSi is possible with longer dwell time [8] or multiple PLA [9].…”
Section: A Silicidation With Pulsed Laser Annealmentioning
confidence: 99%
“…This phenomenon creates a region with different melting points and hence some part of the film (Ni-rich Ni-Si layer) was rapidly solidified into glassy state, where the other (NiSi 2 layer) solidifies in a slower speed which then undergoes a liquid phase epitaxial regrowth taking a Si substrate as the template as in the case of NiSi 2 layer at the film/Si interface. Figure 17 The XTEM micrograph of the sample after (a) single-pulsed LA at 0.5 J/cm 2 and (b) 20 pulses LA at 0.3 J/cm 2 (36,37).…”
Section: Ni Silicides Formation Using Multiple-pulsed Laser Annealingmentioning
confidence: 99%
“…This observation signifies that a multiple-pulsed LA is capable to facilitate the silicide formation at even lower thermal budget. Figure 16 The XRD spectra of the Ni 1-x (Ti) x /Si sample after (a) single-pulsed and (b) 20 pulses LA at varying laser fluences (36,37).…”
Section: Ni Silicides Formation Using Multiple-pulsed Laser Annealingmentioning
confidence: 99%